Improving Information Writing Skills Using Standard Vocabulary Through Audio Visual Media - Wahiburrokhman, M; Bagiya, Bagiya; Ratnaningsih, Arum (Jurnal Pendidikan Amartha, 2023)
This research is a classroom action research that aims to improve writing skills using standard vocabulary in class III students at SDN Sidowangi through audio-visual media. This study uses the research design of Kemmis and Mc. Taggart which consists of two cycles and each cycle consists of planning, implementing actions, observing and reflecting. This research was carried out at SDN Sidowangi involving 14 students consisting of 8 boys and 6 girls. Based on the results of initial observations on students at Sidowangi Elementary School, especially in class III, there are still many who have not been able to write a sentence using the right vocabulary so it needs to be improved. The results showed that the action was obtained. At the pre-cycle stage, the ability to write information using standard vocabulary in class III obtained an average score of 43.13 and in cycle I obtained an average score of 51.4. Both of these scores indicate that from pre-cycle to cycle I there was an increase of 8.27 points. Furthermore, in cycle II students obtained a class average of 85.33. Thus, from cycle I to cycle II students' writing skills using the standard vocabulary of class III at SDN Sidowangi increased by 33.93. It can be concluded that the use of audio-visual media in writing skill material using standard vocabulary can improve student learning outcomes.